In the Face of Climate Change, Coral Reservoirs with Restoration Potential: A Case Study in Utría Cove, Eastern Tropical Pacific - Maria Gabriela Quirama; Juan Felipe Lazarus; Mateo López-Victoria (Diversity, 2025)
The limited research in Utría Cove has hindered our understanding of marginal coral areas in a rapidly changing ocean. To better understand how marginal reefs could serve as coral reservoirs where local communities could actively be involved, we assessed the ecological attributes of Utría’s coral areas, documented the impact of the 2023–2024 El Niño event, and conducted a SWOT analysis to frame the restoration potential. The current state shows a reduction of 1.4 ha in La Chola reef, where the average live coral cover is 24% and algal cover is 41%. The other two coral communities assessed (Diego and Punta Diego) showed coral cover between 14% and 17%, and algal cover between 42% and 50%, respectively. No significant differences were found in structural complexity, benthic cover, and macroinvertebrates; only fish richness was significantly higher at Punta Diego. Based on previously documented higher coral cover, the three areas need interventions (i.e., active restoration), especially considering the widespread bleaching recorded (temperatures up to 31.4 °C; sustained mean temperatures of ~30 °C ± 0.43), associated with El Niño. The SWOT analysis identified four weaknesses (e.g., logistical challenges), four threats (e.g., illegal fishing), six strengths, and six opportunities that highlight the potential to engage locals in restoration by providing economic alternatives and boosting regional initiatives.